Synthesis, characterization of mesoporous silica powders and application to antibiotic remotion from aqueous solution: effect of supported Fe-oxide on the SiO2 adsorption properties - Brigante, Maximiliano Eduardo (2014)
The remotion of the antibiotic minocycline (MC) on mesoporous silica (SiO2) and on the binary system iron(III) oxide–SiO2 (Fe-SiO2) has been studied in batch experiments by performing adsorption isotherms/kinetics under different conditions of pH, KCl concentration and temperature. The adsorption of MC on the studied materials is strongly dependent on pH, increasing as pH decreases. The incorporation of a low concentration of iron (1.03 wt.%, mainly as amorphous Fe2O3) on the SiO2 matrix not only increases the adsorption capacity but also changes the adsorption mechanism. The adsorption of MC on SiO2 strongly decreases as KCl concentration increases but it is not significantly affected by varying the temperature. This is attributed to electrostatic attractions and H-bond formations between dimethylamino, amide, carbonylic and phenolic groups of the antibiotic and the functional groups of silica particles. The adsorption of MC on Fe-SiO2, on the contrary, strongly increases as temperature increases but remains invariable by varying the KCl concentration. This suggests that the formation of inner-sphere complexes between the functional groups of the antibiotic and the active sites of Fe2O3 plays a key role on the adsorption mechanism. The analysis of adsorption thermodynamic parameters is also reported and discussed. The synthesized materials can act as excellent adsorbents for environmental and engineering processes.